Animal Welfare: eine empirische Analyse landwirtschaftlicher Frames; Animal Welfare: An Empirical Analysis of Agricultural Frames - Ingke Deimel; Annabell Franz; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2012)
Nach den aktuellen Erkenntnissen der nutztierwissenschaftlichen Forschung rekurriert das Verständnis von Animal Welfare auf vier Kriterien: Haltungssystem, Management, Tiergesundheit und Tierverhalten (KEELING und KJÆRNES, 2009). Es ist jedoch unklar, inwieweit sich dieses Verständnis auch in der landwirtschaftlichen Praxis wiederfindet. In der vorliegenden empirischen Studie wird erstmals mit Hilfe einer Faktorenanalyse das Animal-Welfare-Verständnis konventioneller deutscher Schweinemäster untersucht. Hierzu wird auf das theoretische Konzept des Framing zurückgegriffen. Die Ergebnisse zeigen, dass bei den Befragten zwei Frames von Animal Welfare existieren: Während Kriterien des (natürlichen) Tierverhaltens im Verständnis der befragten Landwirte eine untergeordnete Rolle spielen, findet eine biologisch-technische Definition von Animal Welfare deutliche Zustimmung (Quelle: Verlag) – – According to the current state of livestock sciences the assessment of animal welfare nowadays is based on four dimensions, i. e. good housing, good feeding, good health and appropriate behaviour (KEELING and KJÆRNES, 2009). However, it remains unclear to what extent this understanding of animal welfare is shared by farmers. The aim of the present study is thus to estimate the concerns of conventional German pig farmers about animal welfare by means of a factor analysis. For this purpose the theoretical concept of framing is applied. The results show that two animal welfare frames exist among respondents. While an animal welfare understanding that focuses on biological and technical aspects is highly approved, criteria based on (natural) animal behaviour play only a minor role.
Keywords: 330; Tierschutz; Schweinehaltung; Faktorenanalyse